Parents Knowledge and Experiences of Child TB Patients about Medicine Administration in the Intensive Phase - Sari, Ethyca; Kristina, Tri Nur; Sujianto, Untung (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Children with pulmonary tuberculosis (TB) who are undergoing intensive phase of treatment often experience negative things, resulting in disobedience in taking medication. Exploration of the experiences of pediatric TB patients in the treatment process needs to be known as information for management from the aspect of drug adherence. The role of parents in overcoming these problems is very important, so it is necessary to know the extent of their knowledge about pulmonary TB disease. METHODS: A qualitative study to explore the experiences of pediatric TB patients was conducted by interviewing 15 patients aged 8–12 years. In addition, a questionnaire was filled out to assess the knowledge about TB of the patient’s parents. The results of the recorded interviews were written and analyzed using the thematic method, while the results of the questionnaire from parents were analyzed descriptively. RESULTS: The results of the questionnaire showed that as many as ten respondents (66.6%) had a sufficient level of knowledge with 9 (60%). Analysis of the data using the Spearman rank test obtained a significance value (p) of 0.11 where p < 0.05, which means there is no relationship between adherence to medication for pulmonary tuberculosis in children and the knowledge of parents in the intensive phase. CONCLUSION: Parental knowledge is sufficient or good does not guarantee that it can change the behavior of individuals or children in complying with the treatment in the intensive phase, although knowledge plays an important role in increasing adherence to taking medication in the intensive phase, there may be other factors that influence so that there is no relationship.